Acid ceramidase treatment enhances the outcome of autologous chondrocyte implantation in a rat osteochondral defect model. Issue 4 (April 2016) - Frohbergh, M.E.; Guevara, J.M.; Grelsamer, R.P.; Barbe, M.F.; He, X.; Simonaro, C.M.; Schuchman, E.H.
Summary: Objective: The overall aim of this study was to evaluate how supplementation of chondrocyte media with recombinant acid ceramidase (rhAC) influenced cartilage repair in a rat osteochondral defect model. Methods: Primary chondrocytes were grown as monolayers in polystyrene culture dishes with and without rhAC (added once at the time of cell plating) for 7 days, and then seeded onto Bio-Gide ® collagen scaffolds and grown for an additional 3 days. The scaffolds were then introduced into osteochondral defects created in Sprague–Dawley rat trochlea by a microdrilling procedure. Analysis was performed 6 weeks post-surgery macroscopically, by micro-CT, histologically, and by immunohistochemistry. Results: Treatment with rhAC led to increased cell numbers and glycosaminoglycan (GAG) production (∼2 and 3-fold, respectively) following 7 days of expansion in vitro . Gene expression of collagen 2, aggrecan and Sox-9 also was significantly elevated. After seeding onto Bio-Gide ®, more rhAC treated cells were evident within 4 h. At 6 weeks post-surgery, defects containing rhAC-treated cells exhibited more soft tissue formation at the articular surface, as evidenced by microCT, as well as histological evidence of enhanced cartilage repair. Notably, collagen 2 immunostaining revealed greater surface expression in animals receiving rhAC treated cells as well. Collagen 10 staining was not enhanced. Conclusion: The results further demonstrate the positive effects of rhAC treatment on chondrocyte growth and phenotype in vitro, and reveal for the first time the in vivo effects of the treated cells on cartilage repair.